Circadian rhythm, hypoxia, and cellular senescence: From molecular mechanisms to targeted strategies - Nie, Tong; Nepovimova, Eugenie; Wu, Qinghua (European journal of pharmacology, 2025)
Cellular senescence precipitates a decline in physiological activities and metabolic functions, often accompanied by heightened inflammatory responses, diminished immune function, and impaired tissue and organ performance. Despite extensive research, the mechanisms underpinning cellular senescence remain incompletely elucidated. Emerging evidence implicates circadian rhythm and hypoxia as pivotal factors in cellular senescence. Circadian proteins are central to the molecular mechanism governing circadian rhythm, which regulates homeostasis throughout the body. These proteins mediate responses to hypoxic stress and influence the progression of cellular senescence, with protein Brain and muscle arnt-like 1 (BMAL1 or Arntl) playing a prominent role. Hypoxia-inducible factor-1α (HIF-1α), a key regulator of oxygen homeostasis within the cellular microenvironment, orchestrates the transcription of genes involved in various physiological processes. HIF-1α not only impacts normal circadian rhythm functions but also can induce or inhibit cellular senescence. Notably, HIF-1α may aberrantly interact with BMAL1, forming the HIF-1α-BMAL1 heterodimer, which can instigate multiple physiological dysfunctions. This heterodimer is hypothesized to modulate cellular senescence by affecting the molecular mechanism of circadian rhythm and hypoxia signaling pathways. In this review, we elucidate the intricate relationships among circadian rhythm, hypoxia, and cellular senescence. We synthesize diverse evidence to discuss their underlying mechanisms and identify novel therapeutic targets to address cellular senescence. Additionally, we discuss current challenges and suggest potential directions for future research. This work aims to deepen our understanding of the interplay between circadian rhythm, hypoxia, and cellular senescence, ultimately facilitating the development of therapeutic strategies for aging and related diseases.
Keywords: Animals; Hypoxia; Cell Hypoxia; transkripční faktory ARNTL; cílená molekulární terapie; lidé; stárnutí buněk; faktor 1 indukovatelný hypoxií - podjednotka alfa; Circadian Rhythm; signální transdukce; Signal Transduction; cirkadiánní rytmus; hypoxie; Hypoxia-Inducible Factor 1, alpha Subunit; zvířata; ARNTL Transcription Factors; Molecular Targeted Therapy; Cellular Senescence; hypoxie buňky; Humans